2023
DOI: 10.3390/en16041681
|View full text |Cite
|
Sign up to set email alerts
|

Energy Harvesting for Wearable Sensors and Body Area Network Nodes

Abstract: This paper aims to present new trends in energy-harvesting solutions pertaining to wearable sensors and powering Body Area Network nodes. To begin, we will present the capability of human beings to generate energy. We then examine solutions for converting kinetic and thermal energy from the human body. As part of our review of kinetic converters, we survey the structures and performance of electromagnetic, piezoelectric, and triboelectric systems. Afterward, we discuss thermal energy converters that utilize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…In a brief form, the structure and principles of the operation of circuit configurations suitable for building power management systems are considered. Furthermore, some of the publications [17,20,21] analyze and compare in tabular form the basic structural or electrical parameters of various types of piezoelectric elements or power management systems, confirming their effectiveness.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In a brief form, the structure and principles of the operation of circuit configurations suitable for building power management systems are considered. Furthermore, some of the publications [17,20,21] analyze and compare in tabular form the basic structural or electrical parameters of various types of piezoelectric elements or power management systems, confirming their effectiveness.…”
Section: Introductionmentioning
confidence: 89%
“…In order to satisfy the above-mentioned need, an analysis of published review papers [12][13][14][15][16][17][18][19][20][21][22] has been performed. Moreover, the published review articles can be divided into two groups in view of the trends related to the continuous improvement in the approaches to designing electronic circuits, as well as the synthesis of new materials for the construction of piezoelectric elements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research very often focuses on wearable devices as the most promising use-cases for energy harvesters [7]. It is suggested that a combination of different ambient energy sources can maximise the output power available to be reused [8].…”
Section: State Of Researchmentioning
confidence: 99%
“…Hence, the question of how to provide a sustainable energy supply to IoT devices is becoming an increasingly important issue for the success of next-generation IoT networks. Energy from electromagnetic fields (EMFs) is considered a promising new energy source for ultra-low-power consumption IoT devices, such as wearable devices and IoT sensors [7][8][9][10][11][12][13][14]. Radiofrequency (RF) energy harvesting, which is the conversion of energy from EMFs emitted from devices in wireless cellular networks (2G, 3G, 4G and Energies 2023, 16, 5622 2 of 22 5G) and local networks (IEEE 802.11) into usable electrical energy, has several advantages compared to the rest of the resources [15].…”
Section: Introductionmentioning
confidence: 99%